2008
DOI: 10.1097/olq.0b013e31818eb923
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Sexually Transmitted Disease Prevention and Control Strategies: Tailoring for African American Communities

Abstract: African Americans carry the largest disease burden for bacterial sexually transmitted diseases (STDs) in the United States. These infections can have a devastating impact on sexual and reproductive health if they are not diagnosed and treated. Traditionally, public health efforts to prevent and control bacterial STDs have been through surveillance, clinical services, partner management, and behavioral intervention strategies. However, the persistence of disparities in STDs indicates that these strategies are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 75 publications
1
22
0
2
Order By: Relevance
“…In addition, our procedures did not control for several contributing factors that are known to affect sexual behavior, such as family structure, neighborhood characteristics, and family income. Finally, the ultimate target of sexual risk programs must be a reduction in the prevalence of HIV/AIDS and other STDs (Barrow et al 2008). A study to address this goal would require implementation on a much larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our procedures did not control for several contributing factors that are known to affect sexual behavior, such as family structure, neighborhood characteristics, and family income. Finally, the ultimate target of sexual risk programs must be a reduction in the prevalence of HIV/AIDS and other STDs (Barrow et al 2008). A study to address this goal would require implementation on a much larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…Behavior change remains a backbone of interventions in higher-income nations, although results have been somewhat disappointing as with Project EXPLORE/HIVNET 015 Koblin et al 2003Koblin et al , 2004Colfax et al 2004Colfax et al , 2005Salomon et al 2009). Combination interventions are now being explored (Barrow et al 2008;Corsi and Booth 2008;Buchbinder 2009;Rotheram-Borus et al 2009;Burns et al 2010;Cohen et al 2010;Crawford and Vlahov 2010;DeGruttola et al 2010;El-Bassel et al 2010;Read 2010;Reynolds and Quinn 2010), as are behavioral approaches with a better base in evidence Harshbarger et al 2006;Lyles et al 2006;Wingood and DiClemente 2006;Margaret Dolcini et al 2010). One strategy has been a conspicuous failure, namely "abstinence only" education, discovered to be associated with higher pregnancy rates than more comprehensive approaches that also highlighted STD prevention with condom use (Ott and Santelli 2007;Kohler et al 2008;Trenholm et al 2008).…”
Section: Prevention Of Hiv In High-income Nationsmentioning
confidence: 99%
“…Introducing tailored prevention interventions and building support centers could increase HIV/AIDS knowledge and related capacities towards risk reduction among those at risk or living with HIV/AIDS [20]. Tailored interventions, such as Sisters Informing Sisters about Topics on AIDS (SISTA) and Coping with HIV and AIDS in the Rural Southeast (CHASE), have infused cultural elements towards more effective education and capacity building in safe sex negotiation with partners [22,23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…Another review identified only 19% of HIV risk reduction interventions published between 1991 and 2010 targeting African Americans or Hispanics [26]. Existing STI behavioral interventions for African Americans have had only a modest impact in eliminating the HIV burden [24]. …”
Section: Introductionmentioning
confidence: 99%